2018
DOI: 10.1001/jama.2018.0245
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Low-Fat vs Low-Carbohydrate Diet on 12-Month Weight Loss in Overweight Adults and the Association With Genotype Pattern or Insulin Secretion

Abstract: clinicaltrials.gov Identifier: NCT01826591.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
400
1
12

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 570 publications
(455 citation statements)
references
References 43 publications
(128 reference statements)
15
400
1
12
Order By: Relevance
“…Because overall weight change and attrition did not differ between the two diet‐type treatment arms (low‐carbohydrate and low‐fat) , data were collapsed across the two arms, as has been done previously . Furthermore, because diet type was the randomization factor in the parent study, it was included as a covariate in all analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because overall weight change and attrition did not differ between the two diet‐type treatment arms (low‐carbohydrate and low‐fat) , data were collapsed across the two arms, as has been done previously . Furthermore, because diet type was the randomization factor in the parent study, it was included as a covariate in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention lasted 12 months. No mean differences in weight change (the primary outcome) were found between treatment arms, with weight losses of 5 to 6 kg, on average, at 12 months .…”
Section: Introductionmentioning
confidence: 91%
“…We can investigate the effects of one component addition or deletion on health or disease incidence, 24 but it will be much more difficult to compare different dietary patterns. 51 Close adherence only to one diet seems to betray the nature of humans' feeding behavior and needs forceful will. The precise record and analysis of daily calorie intake and nutrition compositions are other technical barriers until now.…”
mentioning
confidence: 99%
“…4 Although a topic of scientific and public debates, extensive and rigorous evidence review finds no clear evidence from systematic reviews and meta-analyses of randomized controlled trials (RCTs) for superiority from either high-or low-CHO diets for weight control or for diabetes care. [5][6][7][8] Most clinical guidelines allow flexibility over CHO content, to suit personal preference, but the role of high-CHO foods as sources of micronutrients appears rather neglected in this debate. 9,10 Very limited previous evidence has suggested that micronutrient content and adequacy may be compromised.…”
mentioning
confidence: 99%